Market liquidity after the financial crisis - Tobias Adrian; Michael Fleming; Erik Vogt (Federal Reserve Bank of New York, 2016)
This paper examines market liquidity in the post-crisis era, in light of concerns that regulatory changes might have reduced banks' ability and willingness to make markets. We begin with a discussion of the broader trading environment, including a discussion of regulations and their potential effect on dealer balance sheets and market making, but also considering plausible alternative drivers of market liquidity. Using both high- and low-frequency data on U.S. Treasury securities and corporate bonds, we then investigate empirically whether liquidity has in fact deteriorated, and we review market behavior around three key post-crisis events. Overall, our findings, and those of recent papers we survey, do not suggest a significant decline in bond market liquidity. We conclude with ideas for future research, including the evaluation of additional data, methodological improvements, and closer analyses of liquidity risk and the interplay between market liquidity and funding liquidity.
Keywords: G12; G21; G28; 330; liquidity; market making; Treasury market; corporate bonds; regulation